Implementation of Internal Quality Assurance in Polytechnics: Evidence from Ghana - Mensah, Mary Afi (European Scientific Journal, ESJ, 2016)
Quality assurance in higher education has become a global issue. There has been a growing interest of governments around the world that higher education institutions in their countries need to provide quality education to their students. This study investigated the implementation of internal quality assurance in two purposively selected Ghanaian Polytechnics. Qualitative methodology was employed using in-depth interviews based on a case study research design. The participants indicated that the internal quality assurance systems and practices in place in the Polytechnics included areas such as the availability of internal quality assurance policy, teaching and learning processes, curriculum design, evaluation and review, research performance, extension activities, student assessment practices, student-lecturer assessment and student support services. Infrastructure challenges, funding and budget constraints, human capacity constraints and lack of quality culture were found to militate against the implementation of quality assurance in the Polytechnics. It was recommended that Ghanaian Polytechnics should have clear policies and associated procedures for the assurance of quality and standards of their programmes and awards. They should commit themselves explicitly to the development of quality culture and quality awareness. Also, the necessary learning facilities, resources and support systems should be provided by the Polytechnics to ensure quality of teaching and learning. The products, environments, programmes and services provided by the Polytechnics should be accessible and usable, to the greatest extent possible, by all categories of students. Assistive devices should be provided for persons with disabilities where needed. Building internal capacity for quality assurance was also recommended.